NILAI MORAL DALAM NOVEL RANAH 3 WARNA KARYA AHMAD FUADI (TINJAUAN SOSIOLOGI SASTRA) - Erlina Erlina (Ensiklopedia Education Review, 2023)
This research is motivated by moral values in Ranah 3 Warna novel by Ahmad Fuadi (reviews sociology of literature). Moral values is a meaningful and have associated ethical behavior should be a reflection of morality in terms of good, bad, right, or wrong. There are many kind of moral values, including loyalty, virtue, honor, truth, respect, friendliness, integrity, and tasks. This study aimed to describe the moral values in Ranah 3 Warna novel by Ahmad Fuadi in reviews sociology of literature. The research is a qualitative study using descriptive methods. This research data is soft data that word form, sentence phrase that has a moral value in Ranah 3 Warna novel by Ahmad Fuadi. The data used in this study are words or sentences, the source of the data in the study were classified into two: (1) The primary data sources such as text from Ranah 3 Warna novel by Ahmad Fuadi published by PT Gramedia Pustaka Utama Jakarta in 2011 as many as 469 pages, from the aspect of moral values, and (2) secondary data sources are form papers, books, and articles that have relevance to strengthen the argument and supplement the results of the research. Data collection techniques in this study are: (1) read the novel repeatedly to understand the content of the novel, (2) code the quote in Ranah 3 Warna novel containing of moral values, and (3) records the data encoded on Ranah 3 Warna novel attached to the research instruments. While the steps in analyzing data are: (1) read data that has been collected, (2) classifying the data containing of moral values in the tables of research instruments, (3) draw conclusions from the data analysis, and (4) write the reports. The results of this study stated that there are moral values of the characters in Ranah 3 Warna novel by Ahmad Fuadi. Moral values that found are conscience, freedom and responsibility, values and norms, and rights and obligations.Keywords: moral values, novel, literary sociology.